Pendekatan Fiqh terhadap Zina dalam Kitab Alfiyyah Zubad pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Fiqh Approach to Zina in the Book Alfiyyah Zubad in the Book Subject at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Zahwa Musarofah; Nasywa Maulida Arrahma; Kykky Brillian Febriana; Adellya Arya Ardianti; Safna Eka Fadilla (DIRASAH: Jurnal Kajian Islam, 2025)
This study examines the Islamic jurisprudence (fiqh) approach to zina (adultery) as contained in Imam Ibn Ruslan Asy-Syafi'i's Alfiyyah Zubad, a book taught in the Islamic texts course at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The background of this research is based on the importance of understanding Islamic jurisprudence (fiqh jinayah), particularly the laws of zina (adultery), in shaping the morals of students while maintaining the relevance of classical teachings to the context of modern Islamic boarding school education. This study aims to analyze the legal content of zina (adultery) in the Alfiyyah Zubad book, its teaching methods in Islamic boarding schools, and the educational values it embodies. The method used is a qualitative-descriptive approach, with data collection techniques through classroom observations, interviews with ustadz (teachers) and students, and a textual analysis of the book. The results indicate that Alfiyyah Zubad contains a comprehensive explanation of zina, encompassing its definition, conditions, proof, and punishment, emphasizing the principle of caution (dar' al-hudud bisy-syubuhat). This book is taught in Islamic boarding schools using the bandongan and sorogan methods, which combine legal and moral aspects. In conclusion, the fiqh approach in Alfiyyah Zubad serves not only to foster an understanding of Islamic law but also as a medium for internalizing the values of purity, honor, and moral responsibility among students.